Theory of the reflective localization of sound sources - BUDZYŃSKI, Gustaw (Archives of Acoustics, 1986)
In order to explain the mechanism of distance localization of sound sources with hearing, a hypothesis was stated that a "situation analyzer" exists in the man central nervous system. The analyzer is capable of perceiving not only the direction of direct and reflected sounds reaching the listener, but also the position of reflecting surfaces, distance of the reflection points and corresponding angles, for the so-called early reflected sounds.On the basis of the above mentioned hypothesis, and considering certain acoustic situations and some visual analogies, foundations for a new theory of the reflective localization of sound sources have been created. Suggestions important for the psychoacoustics in general as well as for room – acoustics and studio – technique applications have been outlined.